The engaged historian : perspectives on the intersections of politics, activism and the historical profession - Berger, Stefan (Making sense of history, 2019)
On the surface, historical scholarship might seem thoroughly incompatible with political engagement: the ideal historian, many imagine, is a disinterested observer focused exclusively on the past. In truth, however, political action and historical research have been deeply intertwined for as long as the historical profession has existed. In this insightful collection, practicing historians analyze, reflect on, and share their experiences of this complex relationship. From the influence of historical scholarship on world political leaders to the present-day participation of researchers in post-conflict societies and the Occupy movement, these studies afford distinctive, humane, and stimulating views on historical practice and practitioners.